ChemInform Abstract: Ion Intercalation into Two‐Dimensional Transition‐Metal Carbides: Global Screening for New High‐Capacity Battery Materials. Issue 14 (April 2015) - Eames, Christopher; Islam, M. Saiful
Abstract: A screening of (Li +, Na +, K +, or Mg 2+ ) intercalated 2D M2 C compounds (M: Sc, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta) with F‐, H‐, O‐, and OH‐functionalized surfaces as potential battery electrodes is performed by DFT methods.